Comparative Study of Antioxidant Test of Combination Pomegranate Peel and Rice Husk Extract in Body Scrub Formula - Nadya Tsurayya; Risca Wulandari (Jurnal FARMASIMED (JFM), 2026)
Background: Antioxidant molecules have the ability to convert free radicals into harmless molecules. Antioxidants can be formed in the body or obtained from external sources, either in the form of enzymes, minerals, or non-enzymatic compounds such as vitamins A, C, and E. Pomegranate peel contains bioactive compounds in the form of phenolics, flavonoids, and tannins. The use of rice husks is relevant because, as a natural exfoliator, they also contain phenolic/flavonoid antioxidants. Research objective: To assess and compare the antioxidant activity of body scrubs made from rice husk extract and pomegranate peel. Research method: The methods used were maceration, antioxidant testing using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, and physical stability testing of the preparations. The antioxidant activity test results showed that the IC50 value of pomegranate peel extract was 7.65 ppm. Results: The antioxidant activity test results of preparations combining the extract with rice husks showed an IC50 value of 3.65 ppm. This indicates that F3 has very strong antioxidant activity. Based on organoleptic testing, homogeneity, pH, spreadability, adhesiveness, and cream type in Formulas 0, 1, 2, and 3. Conclusion: Pomegranate peel extract and rice husks can be successfully combined to produce a stable body scrub formula with sustained antioxidant activity